Seguridad eléctrica en el medio ambiente hospitalario - Azpiroz L., Joaquín; Medina B., Verónica; Rode M., Mónica; Ortega V., Patricia; Cadena A, Teófila; Berdichevsky, Fernando (Revista Mexicana de Ingenieria Biomedica, 2018)
In this article, the basic concepts of electrical safety in hospitals are reviewed. The maximim acceptable values of leakage currents for a safe electrical enviroment are presented. Also included are procedures for inspection and preventive maintenance of the electrical installation and electromedical equipment.